Synergistic effect of antagonistic microflora and farmyard manure (FYM) to reduce wilt disease in chickpea caused by Fusarium oxysporum f sp ciceri - KHAN, MUDASSER AHMED; GANGOPADHYAY, S; SINGH, SHALANDRA (The Indian Journal of Agricultural Sciences, 2014)
Wilt disease of chickpea caused by Fusarium oxysporum f sp ciceri (Pudwick) Synd. and Hans. is serious problems across the country. The experiment was conducted at the farm College of Agriculture, Rajasthan Agricultural University, Bikaner in for two crop seasons 2007-08 and 2008-09 to manage the wilt disease of chickpea. Chickpea variety RSG- 44 was used for this experiment. For the purpose, two antagonist, i.e. Trichoderma harzianum and Pseudomonas fluorescens were applied as seed treatment (alone @ 8 g/ kg seeds; in combination of both bioagents @ 4 g + 4 g/ kg seeds) and soil application (alone @ 10 kg/ ha; in combination of both bioagents @ 5 kg + 5 kg/ ha) along with FYM @ 5, 10, and 15 tonnes/ ha in the field. Minimum wilt disease incidence 23.65% and 25.35% was found in the treatment T12: T. harzianum+P. fluorescens seed treatment (4+4) kg/seed) and soil application (5+5) kg/ha along with FYM @15 tonnes/ h followed by T11:T. harzianum +P. fluorescens seed treatment (4+4) kg/seed) and soil application (5+5) kg/ha along with FYM @10 tonnes/ ha (27.67 and 28.61%) and T8: P. fluorescens ST (8 g/ kg seed + SA (10 kg/ h + FYM 15 tonnes/ha (28.51 and 29.48%) in 2007-08 and 2008-09 under field conditions respectively. The plant growth, i.e. root and shoot lengths, dry weight and seed yield were found higher when T. harzianum and P. fluorescens were used along with higher dose of FYM, i.e. 15 tonnes/ha. A significant variation was recorded among the treatments. The organic carbon content of the soil was increased by increasing the dose of FYM from 5 to 15 tonnes/h irrespective of bioagents. The Fusarium population was suppressed by the two bioagents used alone or in combinations. The population of T. harzianum and P. fluorescens was higher in rhizosphere soil when FYM was applied at higher dose (15 tonnes/ha). Our result findings indicate that microbial bioagents and FYM have synergistic effect on reducing the wilt incidence in chickpea and promote the plant growth significantly.